The challenges of pedagogical supervision in teaching in Tocantins: a reflection on the curriculum document (Research, Society and Development, 2021)
This study aims to understand the role of the Pedagogical Supervisor in the educational process and teaching practice for the development of teaching and learning of students in Basic Education, in the context of implementing the Tocantins Curriculum Document (DCT). The reflection on their competences can contribute to the understanding of their identity and social, political and administrative relevance of their role in the school in terms of supporting teachers' practice, with regard to teaching and learning. It is a bibliographic, documentary, exploratory research, using the deductive method and a qualitative approach. The DCT for Early Childhood Education and Elementary Education was created to improve and guide the teaching and learning process in teaching networks in the Tocantins territory. In a collaborative way, the 139 municipalities organized themselves to comply with the provisions of Article 76 of Resolution CEE-TO/CP No. 024/2019, and Strategy 3.1 of Goal 3, of the State Education Plan, Law No. 2.977, of 8th of July 2015. The results of the investigation indicated that the implementation of the DCT came to ensure the purpose of the school curricula, considering the students' histories, circumstances and local realities, as well as aspects, focused on planning and monitoring; communication and engagement; formative processes; technical support and strengthening of pedagogical management. This denotes a new vision of the Pedagogical Supervisor's practices in the school space, based on a conceptualized intervention in collective action.